The designed housing projects as an alternative for the informal building and their impact in addressing the heterogeneity of the urban escape in the built residential areas (Journal of Engineering, 2012)
The phenomenon of informal building Spread recently in Iraqi residential areas, in general, and in Baghdad, in particular, due to the urgent housing need, on the one hand, and lack of commitment to building controls, on the other hand, to highlight the phenomenon of uncommitted building to controls and housing governing legislation in Iraq, leading to heterogeneity in both building densities and plot areas, and disorder in the urban fabric and urban escape of those areas. Research problem identified as the absence of a clear vision about the General aspects of the phenomenon of informal building in residential street scene, and the role of designed housing projects as a substitute for informal building in built residential areas. The designed housing projects (single or multi story buildings), which designed and constructed accordance to the approved planning and construction regulations and legislation, as one of the solution to the housing crisis, that achieve the harmonious at each level of the urban fabric and urban escape. Accordingly the research hypothesis stated as "the designed housing projects achieve homogeneous formal unity in residential street scene". This paper deals with the role of designed residential projects to reduce the phenomenon of informal building and heterogeneity in the urban escape of built residential areas, by  identifying the phenomenon in residential areas, in general, and in selected area in Baghdad, in particular, first, and present a designed housing projects ( global and local) that achieve homogeneous formal unity at the level of the urban escape, second, the research identified the principles and the elements of the residential street scene and the organization bases that can be a substitute for the informal building and the heterogeneity of the urban escape in built residential areas, third.